Factors Affecting Nurses’ Job Performance at Tidore General Hospital - Dahlan , Fadli; Akbar, Asgar Ari (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
The performance of nurses plays a crucial role in determining the quality of health services in hospitals. This study aims to examine the effect of motivation and work environment on nurses’ performance at Tidore Islands City General Hospital. The total population consisted of 160 nurses, and the sample size was determined using the Krejcie and Morgan table, resulting in 113 respondents. A quantitative research design was applied, and data were analyzed using SPSS version 20. Multiple linear regression analysis, along with t-tests and F-tests, was employed to assess the influence of independent variables on the dependent variable. The results indicate that both motivation (X1) and work environment (X2) have a positive and significant impact on nurses’ performance. These findings suggest that when nurses are provided with adequate motivation and supported by a conducive work environment, their performance improves significantly. Conversely, insufficient motivation and poor working conditions can lead to a decline in performance levels. The study emphasizes the importance of hospital management in creating strategies to enhance motivation and improve the work environment as a means to optimize nurses’ performance. These implications are particularly relevant for hospital administrators and policymakers aiming to strengthen human resource management in the healthcare sector.